Implementation of Motor Vehicle Whitening Program in the Technical Implementation Unit of Local Revenue Management (UPT PPD) Medan Selatan in 2018 - Susi Hariyanti; Badaruddin Badaruddin; Abdul Kadir (Budapest International Research and Critics University, 2021)
National development is the government's effort in realizing the welfare of the people and the state, starting from increasing the standard of living of the community to improving the system for implementing state activities. National development is expected to be evenly distributed throughout the country, both centralized development and development in regions whose power is controlled by the regional government. Phenomenon In the Medan City area, motor vehicle tax is one type of regional tax collected by the Regional Revenue Service of the Province of North Sumatra through the Samsat Joint Office as one of the potential sources of tax revenue, where the Samsat Joint Office has an advantage in the number of vehicle taxpayers who continues to increase every year. From this phenomenon, should there be an increase in the ownership of motorized vehicles with a BK number (tax object) in the area of Medan City, it will have a positive impact on any increase in the amount of motor vehicle tax revenue at the Samsat Joint Office. But in fact, overall motor vehicle tax revenue at the Samsat Joint Office has not been fully realized easily, from the description above, researchers are interested in formulating the problem How to implement the 2018 motor vehicle tax bleaching program in the Regional Revenue Management Technical Implementation Unit (UPT PPD) Medan South and What are the obstacles to motor vehicle tax collection in 2018 in the Regional Revenue Management Technical Implementation Unit (UPT PPD) in South Medan. This type of research used in this study is a qualitative researcher.